A Transdisciplinary Approach to Public Health Law: The Emerging Practice of Legal Epidemiology. - Burris, Scott; Ashe, Marice; Levin, Donna; Penn, Matthew; Larkin, Michelle (Annual review of public health, 2015)
Public health law has roots in both law and science. For more than a century, lawyers have helped develop and implement health laws; over the past 50 years, scientific evaluation of the health effects of laws and legal practices has achieved high levels of rigor and influence. We describe an emerging model of public health law that unites these two traditions. This transdisciplinary model adds scientific practices to the lawyerly functions of normative and doctrinal research, counseling, and representation. These practices include policy surveillance and empirical public health law research on the efficacy of legal interventions and the impact of laws and legal practices on health and health system operation. A transdisciplinary model of public health law, melding its legal and scientific facets, can help break down enduring cultural, disciplinary, and resource barriers that have prevented the full recognition and optimal role of law in public health. Expected final online publication date for the Annual Review of Public Health Volume 37 is March 17, 2016. Please see http://www.annualreviews.org/catalog/pubdates.aspx for revised estimates.